Characterization and expression profiles of cyp19a1a in the schizothoracine fish Schizothorax prenanti. (June 2019) - Yan, Taiming; Cai, Yueping; He, Jiayang; Zhang, Qian; Wang, Xiongyan; Zhang, Songpei; He, Liang; He, Zhi
Abstract: Aromatase plays a central role in ovarian differentiation and development in teleosts. In the present study, we identified a cyp19a1a homologue from the ovary of Schizothorax prenanti and analysed its expression at both the mRNA and protein levels. Cyp19a1a of S. prenanti showed high homology with that of other teleosts, especially S. kozlovi . The ovary and testis were the main sites of cyp19a1a expression in S. prenanti, and cyp19a1a transcript levels peaked in the mid-vitellogenic (MVG)-stage ovary and the mid-spermatogenic (MS)-stage testis. Signals of Cy p19 a1a immunopositivity were detected in the spermatocytes and follicular cells of cortical alveolar-stage and MVG oocytes but not in spermatogonia or spermatids. Taken together, these findings indicate that Cyp19a1a may play an important role in oocyte vitellogenesis as well as spermatocyte development in S. prenanti .